Capacity Enhancement of Uni‐directional In‐band Full‐Duplex Cellular Networks through Co‐channel Interference Cancellation - Ju, Hyungsik; Gwak, Donghyuk; Kim, Sun‐Ae; Lee, Yuro; Kim, Tae‐Joong (ETRI journal, 2018)
As implementation of the in‐band full duplex (IFD) transceiver becomes feasible, research interest is growing with respect to using IFD communication with cellular networks. However, the cellular network in which the IFD communication is applied inevitably suffers from an increase of the co‐channel interference (CCI) due to IFD simultaneous transmission and reception. In this paper, we analyze the performance of a cellular network based on uni‐directional IFD (UD‐IFD) communication, wherein an IFD base station simultaneously supports downlink and uplink transmissions of half‐duplex (HD) users. In addition, a multi‐pair CCI cancellation (MP‐CCIC) method combining CCIC and user pairing is proposed to improve the performance of the UD‐IFD network. Simulation results showed that, compared to a conventional HD cellular network without using CCIC, capacity gain was not obtained in the UD‐IFD cellular network. On the other hand, when applying the proposed MP‐CCIC, the capacity of the UD‐IFD cellular network greatly improved compared to that of an HD cellular network.